Gene polymorphisms associated with immunosuppressant adverse effects in systemic lupus erythematosus: a narrative review - Hamdani, Siva; Hamijoyo, Laniyati; Amalia, Riezki; Barliana, Melisa I. (Frontiers in Genetics, 2025)
Systemic Lupus Erythematosus (SLE) is an autoimmune disease that often requires treatment with immunosuppressant drugs to manage symptoms and prevent organ damage. However, the use of immunosuppressant can be associated with various adverse effects. The spectrum of immunosuppressant toxicity is influenced by various factors such as organ function and medication interval, but genetic variations—particularly single nucleotide polymorphisms—have emerged as critical determinants due to their direct impact on the drug’s pharmacokinetics and pharmacodynamics alteration, also on patient susceptibility to adverse reactions. This review summarizes the current knowledge on gene polymorphisms associated with immunosuppressant adverse effects in SLE patients, focusing on commonly used drugs such as Methotrexate (MTX), Azathioprine (AZA), Cyclophosphamide (CYC), and Mycophenolate Mofetil (MMF). A total of 23 relevant studies published in the last decade were identified through a comprehensive literature search, specifically investigating the relationship between gene polymorphisms and adverse drug reactions in SLE patients. The findings reveal that gene polymorphisms are frequently associated with adverse effects for each immunosuppressant, including MTX (MTHFR and ATIC), AZA (TPMT, NUDT15, ITPA, ABCC4), CYC (CYP2C19, GSTM1, GSTT1, GSTP1, ALDH), and MMF (SLCO1B1, IMPDH1, UGT2B7). Understanding the functional implications of these gene polymorphisms contributes to the application of precision medicine, as they can serve as potential markers for drug selection and dosage adjustment during initiation treatment of immunosuppressant to enhance treatment efficacy, minimize toxicity, and improve outcomes for SLE patients.